Doses de água residuária da suinocultura nas culturas de milho, aveia e soja e suas influencias sobre a meso e macrofauna. - Tessaro, Dinéia (2013)
The swine production is an economic and common management in the Southern region of Brazil, including Paraná Western area. It has also been producing great amounts of waste with high-polluting level, which are commonly loaded into soil as fertilizer in order to increase soil fertility and provide higher crop yields. Such wastes can cause environmental problems when managed improperly, such as loss to soil fauna, an important constituent of soil. Thus, this study aimed at evaluating the tolerance levels of soil fauna by applying different swine wastewater (SWW) doses and the effects on abundance and diversity of meso and macrofauna organisms. The trial was carried out in Campo Bonito-PR, in an agricultural area that has been submitted to a non-tillage management for 13 years. Twenty one 25 m2 plots were set where corn, black oats and soybeans were cropped in different periods. Seven treatments were recorded as: 0, 50, 100, 150 and 200 m3 ha-1 from swine wastewater from a lagoon and there was a treatment using chemical fertilizers, according to the agronomic recommendations for each crop. The seventh treatment corresponded to the parts that were prepared in a remaining native vegetation area. Soil fauna was evaluated by the Tropical Soil Biology Fertility (TSBF) method, Berlese-Tullgren extractor and Pitfall traps. The collected organisms were classified based on their orders and results were evaluated by multivariate statistics, according to the correlation analysis (CA) technique, repeated measures indexes and indexes of Shannon diversity, Pielou evenness (Equitability) and richness of groups. The relation between fauna ecology and soil chemical properties was determined by canonical correspondence analysis (CCA). According to the results, it was observed that the application of swine wastewater/ slurry, stored in lagoon, has affected in a negative way the soil fauna when it received doses greater than 100 m3 ha-1, even though such dose has promoted greater similarity in abundance of organisms with the forest area. It was found out that the sampled orders characterize the forest area according to the simulated conditions: Collembola, Hymenopeptera, Araneae, Diptera, Acari, Hemiptera, Diplura, Protura and Oligochaeta, while Coleoptera order characterized the agricultural soils that are fertilized with swine wastewater. The results also showed that the soil fauna has its abundance affected by season and chemical composition of soil.